Solid-state hydrogen storage materials - Kalibek M. R.; Ospanova A. D.; Suleimenova B.; Soltan R.; Orazbek T.; Makhmet A. M.; Rafikova Kh. S.; Nuraje N. (Springer Science and Business Media LLC, 2024)
The increasing global emphasis on sustainable energy alternatives, driven by concerns about climate change, has resulted in a deeper examination of hydrogen as a viable and ecologically safe energy carrier. The review paper analyzes the recent advancements achieved in materials used for storing hydrogen in solid-state, focusing particularly on the improvements made in both physical and chemical storage techniques. Metal–organic frameworks and covalent-organic frameworks are characterized by their porous structures and large surface areas, making them appropriate for physical adsorption. Additionally, the conversation centers on metal hydrides and complex hydrides because of their ability to form chemical bonds (absorption) with hydrogen, leading to substantial storage capacities. The combination of materials that adsorb and absorb hydrogen could enhance the overall efficiency. Moreover, the review discusses recent research, analyzes key factors that influence performance, and discusses the difficulties and strategies for enhancing material efficiency and cost-effectiveness. The provided observations emphasize the critical significance of improved materials in facilitating the transition towards a hydrogen-based economy. Furthermore, it is crucial to highlight the necessity for additional study and development in this vital field.
Keywords: Hydrogen storage · Solid-state materials · Physical adsorption · Chemical absorption, type of access: open access.